2019
DOI: 10.1039/c8an02171f
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-mediated signal amplification of liquid crystal biosensors for dopamine

Abstract: A new design was developed for detection of dopamine using a boronic acid based amphiphile at aqueous–liquid crystal interface. The detection was highly enhanced in presence of gold nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For example, neurotransmitters (like dopamine) respond rapidly (within only a few milliseconds) to a stimulus, while neuromodulators (like ascorbic acid) respond more slowly to affect the required message between presynaptic terminals and target cells. [286][287][288][289][290][291] In this section, we review different types of goldbased biosensors, which have recently been developed to detect or monitor various neurochemicals in vitro or in vivo. [292][293][294][295][296][297] The efficiency of electrochemical methods could be improved using GNSs for ultra-sensitive determination of different neurological molecules.…”
Section: Gns-based Biosensors For Multiplex Detection Of Markers For ...mentioning
confidence: 99%
“…For example, neurotransmitters (like dopamine) respond rapidly (within only a few milliseconds) to a stimulus, while neuromodulators (like ascorbic acid) respond more slowly to affect the required message between presynaptic terminals and target cells. [286][287][288][289][290][291] In this section, we review different types of goldbased biosensors, which have recently been developed to detect or monitor various neurochemicals in vitro or in vivo. [292][293][294][295][296][297] The efficiency of electrochemical methods could be improved using GNSs for ultra-sensitive determination of different neurological molecules.…”
Section: Gns-based Biosensors For Multiplex Detection Of Markers For ...mentioning
confidence: 99%
“…Liquid crystal (LC) sensors are a powerful and promising detection technique that can transduce and amplify chemical and biological events into visible optical signals with very high sensitivity by employing LCs as a sensing medium. They have the advantages of not requiring intensive labor, molecular labels, or complex instrumentation, which makes them particularly attractive in developing portable and inexpensive devices for point-of-care diagnostics. So far, most of the LC sensors only have been demonstrated to detect single tumor markers such as proteins and enzymes in buffer. To the best of knowledge, simultaneous detection of multiple tumor markers, especially in blood, has not been achieved due to lack of a versatile strategy that can eliminate a potential matrix effect and cross-reactivity of probe/target sets, which greatly hinders practical applications of LC sensors.…”
mentioning
confidence: 99%
“…We have demonstrated that s nal amplification can be achieved with both spin-coated film and sandwiched cell of LC-photopolymer composite [12,31]. In addition, the intensity of the optical response Signal amplification mediated by labeling with gold nanoparticles has been reported in several LC-based biosensors [33][34][35][36][37]. To eliminate the costly and time-consuming procedure of labeling, a number of label-free approaches aimed at enhancing the optical signal and thereby improving detection sensitivity at the LC-solid interface of a sandwiched LC cell were proposed, which include the use of a highly birefringent LC [38,39] and LCphotopolymer composite [12], adjustment of the direction of linearly polarized light for a dye-doped LC [16], modification of the alignment layer by ultraviolet light irradiation [40], and application of a weak electric field to orient LC molecules in a pre-tilted state [41].…”
Section: Signal Amplification Of Single-substrate Detection Through the Control Of Film Thicknessmentioning
confidence: 77%
“…Taking advantage of spin-coating, LC fi thickness can be directly and easily reduced to a desired smaller value (<5 μm) to enhan the optical response. Signal amplification mediated by labeling with gold nanoparticles has been repor in several LC-based biosensors [33][34][35][36][37]. To eliminate the costly and time-consuming p cedure of labeling, a number of label-free approaches aimed at enhancing the optical s nal and thereby improving detection sensitivity at the LC-solid interface of a sandwich LC cell were proposed, which include the use of a highly birefringent LC [38,39] and L photopolymer composite [12], adjustment of the direction of linearly polarized light fo dye-doped LC [16], modification of the alignment layer by ultraviolet light irradiation [ and application of a weak electric field to orient LC molecules in a pre-tilted state [4 Because of the similar working principles between the LC film and LC cell in biodetecti at the LC-glass interface, most of the previously reported signal amplification approach for sandwiched cells would be applicable to the LC film.…”
Section: Signal Amplification Of Single-substrate Detection Through the Control Of Film Thicknessmentioning
confidence: 99%